Meningkatkan Pemahaman Fikih melalui Aplikasi Quizizz: Studi Pra-Eksperimen di MTs Nusantara - Faizatul Ula, Najmil; Muzammil, Muzammil (AS-SABIQUN, 2025)
This study is motivated by the limited research on the use of interactive digital media in Fiqh learning, despite its significant potential to enhance student comprehension in the digital era. The purpose of this research is to measure the effect of using the Quizizz application on students' understanding in Fiqh lessons. The method employed is a quantitative approach with a pre-experimental design using a one-group pretest-posttest model. The sample consisted of 26 seventh-grade students from class VII A at MTs Nusantara Kota Probolinggo for the 2023–2024 academic year, selected using a saturated sampling technique. Data were collected through written tests administered before and after the treatment and analyzed using a paired sample t-test with SPSS version 20. The results indicated a significant difference between the pretest and posttest scores, demonstrating that the use of Quizizz had a positive effect on students’ comprehension. These findings support constructivist learning theory and suggest that digital media can serve as an effective tool in religious education. The main conclusion of this study is that integrating technology into Fiqh learning significantly improves student understanding. The implications include theoretical contributions to the literature on digital-based religious education, as well as practical recommendations for teachers to optimize interactive media in classroom instruction. This study also opens opportunities for further research on the effectiveness of similar digital media in other subject areas.